Women’s Mental Health Literacy in a Conflict-Recovery Setting: Evidence from Telafer, Iraq - Baktash, Mohmmed Qassim (Department of Nursing, Faculty of Medicine, Universitas Diponegoro, 2026)
Background: Mental health literacy plays a significant role in addressing mental health issues. However, evidence regarding mental health literacy among women from Turkmen communities living in post-conflict settings in Iraq remains limited.Purpose: This study aimed to determine the level of mental health literacy and its associated factors among women in the context of conflict recovery in Telafer City, Iraq.Methods: This study employed a descriptive cross-sectional design involving 603 women attending a general hospital in Telafer city. The Arabic version of the Mental Health Literacy scale was used to collect data. Descriptive statistics (mean and standard deviation) were calculated to assess mental health literacy scores. Inferential analyses, including one-way ANOVA, independent-samples t-tests, and multiple linear regression at a 95% confidence level (p < .05), were conducted to assess the relationship between mental health literacy and eight sociodemographic predictors (age, educational level, employment status, marital status, residence, culture, and mental health clinical and family history).Results: The mean mental health literacy score among women was 88.06 (SD = 13.80). Bivariate Pearson’s correlation analysis indicated that age, educational level, employment status, and marital status were significantly associated with mental health literacy (p < .05). However, in the multiple linear regression analysis, only educational level remained a significant predictor (B = 1.342, SE = .456, p = .003, 95% CI [0.447, 2.237]). Conclusion: Mental health literacy among women in Telafer City was moderate. Educational level was the only significant predictor of mental health literacy among Turkmen women. These findings highlight the need for targeted interventions to improve mental health literacy among women in conflict- and war-affected settings. Additionally, the results support the development of mental health education programs tailored for women’s educational levels in Turkmen and Arab communities.